2015
DOI: 10.1186/s40064-015-0957-z
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA treatment for chronic migraine: experience in 52 patients treated with the PREEMPT paradigm

Abstract: OnabotulinumtoxinA (OnabotA) was approved for treatment of chronic migraine (CM) after publication of PREEMPT trials. Thus, we set out to evaluate the efficacy of OnabotA in a series of patients with CM treated according to the PREEMPT protocol.In May 2012 we began to offer OnabotA to patients with CM who did not respond to topiramate and at least one other preventive therapy (beta blocker and/or calcium channel antagonist). We prospectively recorded demographic data and the characteristics of migraine, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
2
21
1
1
Order By: Relevance
“…Since the results from PREEMPT trials were published in 2010 many post-commercialization studies have borne out the efficacy of OnabotulinumtoxinA in CM [13][14][15][16][17][18][19]. A prospective study including 254 patients [16] with endpoints similar to our study showed lower efficacy rates, perhaps because their patients had already tried three different preventive treatments without response.…”
Section: Discussionmentioning
confidence: 63%
“…Since the results from PREEMPT trials were published in 2010 many post-commercialization studies have borne out the efficacy of OnabotulinumtoxinA in CM [13][14][15][16][17][18][19]. A prospective study including 254 patients [16] with endpoints similar to our study showed lower efficacy rates, perhaps because their patients had already tried three different preventive treatments without response.…”
Section: Discussionmentioning
confidence: 63%
“…Pedraza et al have published a study with 52 patients, and only 23.1% failed to perceive a positive effect after the first procedure. 38 Other studies found a much lower efficacy of treatment when considering number of migraine attacks. 23,39 This higher rate of response may be due to the inclusion of relatively young patients who had only tried two previous preventive treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown similar or lower rates of efficacy. Pedraza et al have published a study with 52 patients, and only 23.1% failed to perceive a positive effect after the first procedure . Other studies found a much lower efficacy of treatment when considering number of migraine attacks .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic migraine management includes acute medication optimization and a preventive pharmacological and non-pharmacological approach 5,6 . Current approved therapies are limited, with poor tolerability, refractory profiles and unfavorable costs 7 .…”
mentioning
confidence: 99%
“…Botulinum toxin A acts on C-unit, but not on Aδ, meningeal nociceptors, inhibiting mechanical nociception to suprathreshold stimuli in peripheral trigeminal neurons, thus decreasing pain. It blocks acetylcholine release at the presynaptic nerve terminal, decreasing neuropeptides and releases other neurotransmitters from sensitized trigeminal endings 2,6,8 .…”
mentioning
confidence: 99%